The use of syntactic structures in written compositions as possible measures of language growth among students of the Basilan City High School - Alano, Angeles (Calsado) 1924- ([Quezon City s.n.], 1968)
Using the formal themes of the students of the Basilan City High School during the school year 1967-1968, the study sought to determine whether the syntactic structures used in written compositions can be used as valid and workable measures for language growth in English.
Thesis (M.A.T. English)--University of the Philippines
Keywords: Grammar, Comparative and general -- Syntax; English language -- Syntax; Basilan City